Intentionality, mind, and language: Phenomenological and analytical approaches - Mabaquiao, Napoleon M. (Animo Repository, 2004)
This study has two main objectives. The first is to evaluate the two controversial claims contained in Dreyfus’s critical review of Searle’s theory of intentionality; namely, that Searle’s theory shares deep affinities with Husserl’s, and that Heidegger’s critique of Husserl’s theory renders Searle’s theory implausible. The second is to make a comparative analysis of the theories of intentionality of Husserl and Searle with a view to establishing which is the better theory in terms of coherence, explanatory power, and (conceptual and ontological) simplicity. Intentionality is an essential feature of consciousness and language, which figures prominently in current discussions on the nature of the mind. Searle’s approach to intentionality represents the analytical approach, while Husserl’s and Heidegger’s represent the two versions of the phenomenological approach—the transcendental-phenomenological approach of Husserl and the existential-phenomenological approach of Heidegger. Dreyfus, on the other hand, is a follower and defender of the Heideggerian approach, who, like Searle, has significant contributions to the development of contemporary philosophy of mind. This study argues for the following. First, the affinities attributed by Dreyfus to Husserl and Searle are either too general or merely superficial; it is their (Searle’s and Husserl’s) differences that are deep and fundamental. Second, the allegedly Heideggerian arguments used by Dreyfus to criticize Searle’s theory are not accurately Heideggerian and are even inconsistent with the basic views of Heidegger. Also, Searle and Heidegger, though working on different philosophical projects, share some basic principles, like the rejection of the Cartesian mind-world split. And third, Searle’s theory is generally more plausible than Husserl’s in the light of the following: Searle’s account of the relationship between consciousness, intentionality, and language is more coherent than Husserl’s; Husserl’s system, unlike Searle’s, requires the postulation of an abstract entity (the noema); and Searle’s conceptual clarity is superior to Husserl’s.